The Effectiveness of the Scrabble Vocabulary Game on High School Students’ English Speaking Accuracy - Muh. Khalid Israr; Dwi Adi Nugroho; Reski (PT Publikasiku Academic Solution, 2026)
This study examines the effectiveness of the Scrabble Vocabulary Game in improving senior high school students’ English speaking ability, particularly their speaking accuracy. The background of this research lies in the persistent difficulties students face in producing accurate spoken English due to limited vocabulary mastery, grammatical errors, and pronunciation problems. In many classrooms, speaking activities are still dominated by conventional teaching methods that do not actively engage students, resulting in low participation and minimal improvement in oral performance. Therefore, innovative and interactive learning media are needed to address these challenges. The purpose of this study was to investigate whether the use of the Scrabble Vocabulary Game significantly improved students’ speaking accuracy and to analyze students’ responses to its implementation. This research employed a quantitative method with a quasi-experimental design involving a pre-test and post-test control group. The sample consisted of 52 eleventh-grade students divided into experimental and control groups. The experimental group was taught using the Scrabble Vocabulary Game, while the control group received conventional instruction. Data were collected through speaking tests and questionnaires and were analyzed using SPSS version 25. The results showed that the experimental group achieved greater improvement in speaking scores than the control group, with a significant difference (p < 0.05). The post-test results indicated substantial improvement in vocabulary use, grammar, and pronunciation. In conclusion, the Scrabble Vocabulary Game is an effective instructional medium for enhancing students’ speaking accuracy and increasing their motivation to learn English.